Pengaruh Pelatihan dan Pengalaman terhadap Kinerja Pegawai - Neni Sri Wahyuni Nengsih (CV. ITTC INDONESIA, 2025)
This study aims to examine the effect of training and work experience on employee performance. The research employed a quantitative approach with a survey method, where data were collected from employees through questionnaires. The collected data were analyzed using multiple linear regression with the help of SPSS. The results showed that training had a positive and significant effect on employee performance. Similarly, work experience was found to have a positive and significant effect on employee performance. Furthermore, training and work experience simultaneously contributed significantly to improving employee performance, with a coefficient of determination (R²) of 0.629, meaning that 62.9% of employee performance variation can be explained by these two variables, while the remaining 37.1% is influenced by other factors. These findings suggest that organizations should optimize training programs and utilize employees’ work experience as strategic efforts to enhance performance.